Efficacy of Curcumin and Piperine as Antioxidant Adjuvant to Intralesional Dexamethasone Injection for Management of Oral Submucous Fibrosis: A Clinical Trial - Nilima Sharma; Abhinav Jain; Sudhir Bahudar; Sukhvinder Singh Oberoi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Oral submucous fibrosis (OSMF) is a well-recognized potentially malignant disorder of the oral mucosa with malignant potential estimated to be 7% to 13%. Both conservative and surgical treatment methodologies have been tried to bring relief from burning sensation, to decrease fibrous bands and to improve mouth opening. The role of curcumin as an anti-inflammatory, antioxidant has not been well established for the treatment of OSMF. Therefore, this study is undertaken. Materials and methods: The patients of OSMF attending the outpatient department of dentistry and otorhinolaryngology constituted the subjects for this study. Both groups were injected twice a week with dexamethasone sodium phosphate 4 mg/mL for 12 weeks. In addition, the test group was asked to take orally tablet TurmixR (curcumin 300 mg and piperine 5 mg) tablet 300 mg thrice daily orally for 3 months. The following outcome variables were measured 3 months posttreatment [burning sensation on visual analog scale, mouth opening (in millimeters) by vernier calipers, percentage relief in symptoms from pretreatment stage, and ultrasonographic evaluation of thickness of fibrotic bands]. Results: The mean change in burning sensation and mouth opening at weeks 3, 5, 7, 9, and 12 was significantly more among test group. The mean change in band length on ultrasonography on both right and left side from pre to mid and posttreatment was significantly more among test group. Conclusion: The commercially prepared avatar of Curcuma longa (turmeric) shows promise in reduction of signs and symptoms of patients with OSMF.